Concise guide to reinforced concrete design to Eurocode 2 - Purcell, Patrick (ICE Publishing, 2022)
Concise Guide to Reinforced Concrete Design to Eurocode 2 explains the principles of limit state design in Eurocode 2 by means of simple worked examples of reinforced concrete design. The book introduces the reader to the basic principles applicable to each section and guides to design elementary reinforced concrete structures. Further practice problems and outline solutions are provided along the way and design charts, tables and formulae are included as design aids throughout. Each chapter contains a summary of the key structural design steps and more in-depth coverage of the design of reinforced concrete structural elements are presented which will be of benefit to any practitioner or student.